Pyrolysis behaviors of coal-related model compounds catalyzed by pyrite. (15th February 2020) - Geng, Haoyao; Li, Lu; Li, Gang; Wei, Yue; Fan, Hongjun; Jin, Lijun; Hu, Haoquan
Graphical abstract: Highlights: The pyrolysis of bibenzyl and benzyl phenyl ether catalyzed by pyrite were studied. Pyrite promotes the initial bond dissociation of model compounds. There is a synergistic effect between tetralin and pyrite in bibenzyl pyrolysis. Abstract: The pyrolysis behaviors of coal-related model compounds (bibenzyl and benzyloxybenzene) were investigated on a fixed-bed reactor catalyzed by pyrite (main component is FeS2 ). The pyrolysis products were analyzed by gas chromatography (GC). The results indicated pyrite could increase the conversion of the model compounds and the yield of liquid and gas, while decrease the char yield. The theoretical calculation results indicated that the pyrite accelerates the initial bond dissociation of parent molecules, thus the radicals can be produced easily. Moreover, the main reason for the decreased yield of char after adding the pyrite is that the large radicals are stabilized on the surface by adsorption, then having little chance to combine with each other to form char. The changes in pyrolysis product distributions with pyrite were also consistent with the calculation results. When adding tetrahydronaphthalene and pyrite simultaneously, there is a significant synergistic effect, which causing the conversion of bibenzyl increased by 14.78 wt% compared with that adding tetrahydronaphthalene or pyrite alone.